Unfolding the Awareness for Women and Children in Vidarbha Region - Mangesh S. Dhore; Gungun Holani (International Journal of Trends in Humanities, 2025)
The concept of “Roots and Wings” as a pathway to empower women and children in Vidarbha region, focusing on the need for both a strong foundation and the freedom to thrive. “Roots” symbolize support systems like education, cultural identity, and community care, while “wings” represent opportunities for growth, self-expression, and independence. Women in Vidarbha often face deep-rooted challenges, including gender inequality, domestic violence, menstrual health, abuse and a lack of awareness about critical health issues like breast cancer. The children, on the other hand, struggle with bullying, child labour, neglection, lack of access to quality education and intense peer pressure. We have visited 21 Villages of Vidarbha region and find out the problems faced by women and children through questionaries and face to face communication. Through rigorous study we have provided proper solution and create awareness among the women’s and children’s of Vidarbha region villages. This research highlights the importance of creating safe environments, spreading awareness, and building resources to support mental and physical well-being. By addressing these issues, we can foster resilience, self-awareness, and confidence, helping women and children in Vidarbha region. The outcomes of this initiative demonstrate that true empowerment emerges when education, empathy, and equality work together at the grassroots level. By nurturing both cultural values and progressive thought, the “Roots and Wings” framework creates a balanced approach to growth. Continued community engagement, health awareness programs, and skill development workshops can further strengthen the confidence of women and children, ensuring sustainable transformation and long-term social development in the Vidarbha region
Keywords: child welfare; gender equality; social transformation; vidarbha community development; women empowerment